ANALISIS ONLINE CUSTOMER REVIEW, ONLINE CUSTOMER RATING, DAN FLASH SALE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SHOPEE - Hermanto, Angga Susilo (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2025)
This study analyzes online customer reviews, online customer ratings, and flash sales on Shopee consumer purchasing decisions. The method used is descriptive quantitative with 40 respondents selected through simple random sampling. The research includes variables online customer reviews, online customer ratings, flash sales, and purchasing decisions. The instrument was tested for validity and reliability. Data were collected through a questionnaire and analyzed using multiple linear regression, classical assumption tests, simultaneous tests (F tests), partial tests (t tests), and the coefficient of determination (R²). The results show that online customer reviews, online customer ratings, and flash sales have a significant effect on purchasing decisions.